Influence of cue exposure on inhibitory control and brain activation in patients with alcohol dependence - Mainz, Verena; Drueke, Barbara; Boecker, Maren; Kessel, Ramona; Gauggel, Siegfried; Forkmann, Thomas (Frontiers in Human Neuroscience, 2012)
Alcohol dependence is a serious condition characterized by persistent desires to drink and unsuccessful efforts to control alcohol consumption despite the knowledge of dysfunction through the usage. Research provides evidence that trying to resist the temptation to drink exerts self-control, a limited resource which is used during all acts of inhibition. In line with this, studies demonstrate an impaired ability to regulate an already initiated response in alcohol dependent and healthy subjects when confronted with alcohol-related stimuli. The study at hand examined the influence of an alcohol exposure on inhibitory processes and related neuronal correlates in alcohol-dependent patients as these associations remain to be elucidated. The inhibition performance of eleven male alcohol-dependent patients during an alcohol exposure was compared with the task performance during a control condition. Behavioral data and neural brain activation during task performance were acquired by means of functional magnetic resonance imaging. The alcohol cue exposure led to subjectively stronger urges to drink which was accompanied by differential neural activation in amygdala and hippocampus. Moreover, the results revealed typical neural activation during inhibition performance across both conditions. Anyhow, we could not detect any behavioral deficits and only subtle neural differences between induction conditions during the performance of the inhibition task within the inferior frontal cortex. The results suggest that although the sample reports a subjectively stronger urge to drink after the alcohol cue exposure this effect was not strong enough to significantly impair task performance. Coherently, we discover only subtle differential brain activation between conditions during the inhibition task. In opposition to findings in literature our data do not reveal that an exposure to alcohol related cues and an thereby elicited cue reactivity results in impaired inhibition abilities.